Improving fatigue performance of surface-damaged Ti-6Al-4V alloy via ultrasonic surface rolling process - Ao Ni; Liu Daoxin; Zhang Xiaohua (MATEC Web of Conferences, 2020)
Surface damages caused by markings, like laser marking and mechanical marking are detrimental to the fatigue performance of the components. To improve the fatigue performance of laser marked or mechanical marked Ti-6Al-4V alloy, ultrasonic surface rolling process (USRP) was performed on Ti-6Al-4V alloy prior to marking. The results showed that laser marking induced a porous and loose oxidized layer which severely decreased the fatigue performance of the substrate. And the mechanical marking slightly decreased the fatigue performance of the substrate due to the local stress concentration at the bottom of the pits. After USRP pretreatment, the detrimental effect of laser marking on the fatigue performance of the substrate was eliminated while the fatigue performance of mechanical marking sample was significantly improved by a factor of 3. That was because the USRP-induced residual compressive stress suppressed the crack early propagation. Key words: Titanium alloy; Fatigue; Ultrasonic surface rolling process; Surface damage; Residual compressive stress; Laser marking, Mechanical marking